Exploring the Link between Helicobacter pylori, Gastric Microbiota and Gastric Cancer - Costantino Sgamato; Alba Rocco; Debora Compare; Kateryna Priadko; Marco Romano; Gerardo Nardone (MDPI AG, 2024)
Gastric cancer (GC) still represents one of the leading causes of cancer-related mortality and is a major public health issue worldwide. Understanding the etiopathogenetic mechanisms behind GC development holds immense potential to revolutionize patients' treatment and prognosis. Within the complex web of genetic predispositions and environmental factors, the connection between Helicobacter pylori (H. pylori) and gastric microbiota emerges as a focus of intense research investigation. According to the most recent hypotheses, H. pylori triggers inflammatory responses and molecular alterations in gastric mucosa, while non-Helicobacter microbiota modulates disease progression. In this review, we analyze the current state of the literature on the relationship between H. pylori and non-Helicobacter gastric microbiota in gastric carcinogenesis, highlighting the mechanisms by which microecological dysbiosis can contribute to the malignant transformation of the mucosa.